2010
DOI: 10.1111/j.1365-2214.2009.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding promotion for infants in neonatal units: a systematic review

Abstract: Breastfeeding/breastmilk feeding is promoted by close, continuing skin-to-skin contact between mother and infant, effective breastmilk expression, peer support in hospital and community, and staff training. Evidence gaps include health outcomes and costs of intervening with less clinically stable infants, and maternal health and well-being. Effects of public health and policy interventions and the organization of neonatal services remain unclear. Infant feeding in neonatal units should be included in public he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 69 publications
2
66
0
7
Order By: Relevance
“…The role of on--site developmental care specialists in providing education and support has been shown to improve clinicians' beliefs related to the effective areas of FCC and the practice of KC (Hendricks--Munoz et al, 2010). Guidelines and policies relating to KC and PT have been shown to be effective in increasing breastfeeding rates when introduced to NICU (Renfrew et al, 2009). Barriers to providing KC, such as a lack of sufficient numbers of trained clinicians, insufficient education and lack of clear protocols have been identified in our study and concur with findings from an Australian survey of NICU nurses in Melbourne, Australia (Chia et al, 2006).…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of on--site developmental care specialists in providing education and support has been shown to improve clinicians' beliefs related to the effective areas of FCC and the practice of KC (Hendricks--Munoz et al, 2010). Guidelines and policies relating to KC and PT have been shown to be effective in increasing breastfeeding rates when introduced to NICU (Renfrew et al, 2009). Barriers to providing KC, such as a lack of sufficient numbers of trained clinicians, insufficient education and lack of clear protocols have been identified in our study and concur with findings from an Australian survey of NICU nurses in Melbourne, Australia (Chia et al, 2006).…”
Section: Main Findingsmentioning
confidence: 99%
“…Through supporting and educating parents in the practices of kangaroo care (KC) and positive touch (PT) neonatal staff can facilitate parental involvement, enhance the bonding process and minimise parental and infant distress (Hunt, 2008;Cleveland, 2008;Renfrew et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted since 1980 have found that babies exposed to skin-to-skin contact with their mothers after birth successfully seek the breast, grasping it and suckling without any help from mother (Bystrova et al, 2009;Renfrew et al, 2010).…”
Section: The Effect Of Kangaroo Care On the Mother-baby Bondmentioning
confidence: 99%
“…Health care workers should be trained in breastfeeding issues and counseling, and they should encourage practices that do not undermine breastfeeding. It is a health care paradox that breastfeeding is not adequately promoted and supported for preterm newborn infants admitted to NICU [54].…”
Section: Donor Human Milkmentioning
confidence: 99%